Controls on microbial activity and tidal flat evolution in Shark Bay, Western Australia - Jahnert, Ricardo; Collins, Lindsay (Blackwell Publishing Ltd, 2013)
Microbial deposits at Shark Bay constitute a diverse living microbial carbonate system, developed in a semi-arid, highly evaporative marine setting. Three tidal flats located in different embayments within the World Heritage area were investigated in order to compare microbial deposits and their Holocene evolution. The stressing conditions in the intertidal–subtidal environment have produced a microbial ecosystem that is trapping, binding and biologically inducing CaCO3 precipitation, producing laminated stromatolites (tufted, smooth and colloform), non-laminated thrombolitic forms (pustular) and cryptomicrobial non-laminated forms (microbial pavement). A general shallowing-upwards sedimentary cycle was recognized and correlated with Holocene sea-level variations, where microbial deposits constitute the younger (2360 years BP) and shallower sedimentary veneer. In addition, sediments have been documented with evidence of exposure during the Holocene, from 1040 to 940 14C years BP, when sea-level was apparently lower than present.Filamentous bacteria constitute the dominant group in the blister, tufted and smooth mat types, and coccus bacteria dominate the pustular, colloform and microbial pavement deposit types. In the subtidal environment within colloform and pavement structures, microbial communities coexist with organisms such as bivalves, serpulids, diatoms, green algae (Acetabularia), crustaceans, foraminifera and micro-gastropods, which are responsible for exoskeleton supply and extensive bioturbation. The internal fabric of the microbial deposits is laminated, sub-laminar, scalloped, irregular or clotted, depending on the amount of fine-grained carbonate and the natural ability of microbial communities to trap and bind particles or induce carbonate precipitation. Nilemah tidal flat contains the thickest (1.3 m) and best-developed microbial sedimentary system; its deposition pre-dated the Rocky Point and Garden Point tidal flats, with the most positive isotope values for δ13C and δ18O, reflecting strong microbial activity in a highly evaporative environment. There is an evolutionary series preserved within the tidal flats reflecting relative ages and degree of salinity elevation.